DESIGN OF SURGE AND ROLL MOTION CONTROL SYSTEM OF ITSUNUSA AUV USING PID CONTROLLER - Teguh Herlambang; Subchan Subchan (JOURNAL ASRO, 2018)
ABSTRACT This paper is about designing motion control system with 2-DOF motion equation to be applied to an Autonomous Underwater Vehicle (AUV) system. The 2-DOF motion equation which consists of surge and roll motion in the form of equations of nonlinear motion. The control system design applied to the ITSUNUSA AUV system uses the Proportional Integral Derivative (PID) method. The simulation results of the PID control system with the motion equation with 2-DOF on the ITSUNUSA AUV system show that the system proves to be stable at a predetermined set-point with an error of 0.01% for surge motion and that with an error of 4.2% for roll motion. Keywords: AUV, motion control, PID